1989
DOI: 10.1097/00000658-198905000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Conservative Versus Early Excision

Abstract: Early excision and grafting of small burn wounds is a generally accepted treatment. Early excision of burn injuries greater than 30% total body surface area (TBSA) in adults, however, has not been universally accepted. In this study, 85 patients whose ages ranged from 17 to 55 years with greater than 30% total body surface area (TBSA) burns were randomly assigned to either early excision or topical antimicrobial therapy and skin grafting after spontaneous eschar separation. Mortality from burns without inhalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(153 citation statements)
references
References 14 publications
3
140
1
2
Order By: Relevance
“…The advantages of early wound closure, demonstrated in several clinical studies, include a diminished hypermetabolic burn response and a decrease in inflammatory mediators, such as IL-6, IL-8 and TNF␣. 25,26 Previous studies using liposomes to transport IGF-I protein and IGF-I cDNA, have demonstrated weight gains and increases in wound healing in burned rats. 18 These studies, however, included recombinant human growth hormone (rhGH) which may directly or indirectly influence wound healing and body weight gains, thus making it difficult to ascertain if one or both of these growth factors were responsible for specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of early wound closure, demonstrated in several clinical studies, include a diminished hypermetabolic burn response and a decrease in inflammatory mediators, such as IL-6, IL-8 and TNF␣. 25,26 Previous studies using liposomes to transport IGF-I protein and IGF-I cDNA, have demonstrated weight gains and increases in wound healing in burned rats. 18 These studies, however, included recombinant human growth hormone (rhGH) which may directly or indirectly influence wound healing and body weight gains, thus making it difficult to ascertain if one or both of these growth factors were responsible for specific effects.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Cationic liposomal complexes attenuate the pro-inflammatory hypermetabolism and post-traumatic acute phase response, 69 treatment with insulin-like growth factor I has been shown to accelerate wound healing by stimulating collagen synthesis and the mitogenicity of fibroblasts and keratinocytes. 61 In a preliminary biodistribution study, using thermally injured rat skin, transfection was detected in myofibroblasts, endothelial cells, and macrophages, including multinucleate giant cells.…”
Section: Growth Factor Delivery By Liposomal Transfectionmentioning
confidence: 99%
“…'Hands on' clinical assessment of the burn depth can be inaccurate and is dependent on the experience of the assessor, the length of time since the insult, and the difference and variation in skin physiology and anatomy between species and changes as the result of topical medications applied 2 . Further complicating this assessment is that burn wounds are dynamic and evolving, sometimes substantially, over the first few days following the insult, and that the injury is rarely of uniform depth throughout the field of damage 2,4 . In humans, early surgical intervention including excision, grafting and acute flaps individualised to each patient is usually performed between days 3 and 5 post-burn of all burns that will not heal within 3 weeks 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is to determine which burns will heal within 3 weeks and this is generally related to the depth of the burn. Early surgical intervention is therefore the treatment of choice for deep dermal and full-thickness burns and should be done before spontaneous demarcation begins and while bacterial contamination remains minimal 3,4 . Mortality rates have been lowered, with survival rate in young patients (17-30 years) with extensive burns [mean 73 % of total body surface area (% of TBSA)] improving from 9 % with delayed skin grafting to 45 % with early excision 5 .…”
Section: Introductionmentioning
confidence: 99%